EFEKTIFITAS MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI KELAS III SD NEGERI 045957 SUKA SEMESTER II T.P. 2019/2020 - Kidah Malem Br Ginting (Pedir Research Institut, 2021)
Abstract:. This study aims to improve students' understanding of learning materials and improve student learning outcomes and student learning activities. The problem solving method in this research is by applying the cooperative learning model of the think pair share type. The results of the study were: 1) Student learning outcomes by applying the TPS type cooperative learning model in the first cycle showed 6 students completed individually, while the class did not complete. In cycle II shows 13 students complete individually and classically complete class with an average cycle I and cycle II are 66.67 and 81.33 with the percentage of classical completeness is 40% in cycle I and 87% in cycle II. The completeness that occurs in cycle I and cycle II is clearly visible in grade III students when student learning is active and students understand the material presented by the researcher so that when the researcher gives formative questions the students are able to answer the questions correctly. Likewise with affective and psychomotor students who have increased. The completeness of the learning outcomes obtained by students was clearly visible when the students in the group discussion were very active and worked on the assignments given by the teacher enthusiastically. This shows that students are getting used to the application of the TPS learning model so that during the learning process students appear active and excited.